Becoming eventful: making the 'more-than' of a youth activist conference matter. Issue 3 (2nd July 2020) - Renold, EJ; Edwards, Victoria; Huuki, Tuija
ABSTRACT: This paper theorises the speculative process of how an arts-based online youth activist resource, AGENDA (www.agendaonline.co.uk ) is becoming eventful and re-mattering youth voice on gender and sexual violence. Utilising the concept of the 'cwrdd' – a Welsh word for gatherings made, found and stumbled upon – we explore how our AGENDA cwrdds attune to, nurture and platform a range of micro-political moments across performances and workshops that entangle human and non-human participants. Inspired by Erin Manning's concept of the 'more-than', we illustrate how the cwrdds carry the past-present-future potentials of what has mattered and is mattering to young people.